Effect of Compensation, Motivation and Organizational Commitment on Employee Perfomance - Hari Lestari; Dadi Komardi; Elnura Elnura (International Journal of Information System and Innovation Management (IJISIM), 2023)
The purpose of this study was to determine the compensation, motivation and organizational commitment to employee performance at PT. Arta Batrindo Branch Pekanbaru. Samples are 45 employees. The sampling technique used is the saturation sampling (census). Data obtained from respondents using data collection tool in the form of a questionnaire. The data analysis used is multiple linear regression analysis using SPSS 19.The results of this study indicate that the variable compensation and no significant effect on the performance of employees of, no motivation variable and no significant effect on the performance of employees of, and variable Organizational Commitment and significant effect on the performance of employees. And simultaneously, variable compensation, motivation and organizational commitment and significant effect on the performance of employees. This means that in deciding to perform work activities are influenced by three variables together, so that when these three variables stronger it will improve employee performance.